High-Dose Vitamin B1 Therapy Prevents the Development of Experimental Fatty Liver Driven by Overnutrition - Kalyesubula, Mugagga; Mopuri, Ramgopal; Asiku, Jimmy; Rosov, Alexander; Yosefi, Sara; Edery, Nir; Bocobza, Samuel; Moallem, Uzi; Dvir, Hay (Disease Models & Mechanisms, 2021)
Fatty liver is an abnormal metabolic condition of excess intrahepatic fat. This condition, referred to as hepatic steatosis, is tightly associated with chronic liver disease and systemic metabolic morbidity. The most prevalent form in humans, i.e. non-alcoholic fatty liver, generally develops due to overnutrition and sedentary lifestyle, and has as yet no approved drug therapy. Previously, we have developed a relevant large-animal model in which overnourished sheep raised on a high-calorie carbohydrate-rich diet develop hyperglycemia, hyperinsulinemia, insulin resistance, and hepatic steatosis. Here, we tested the hypothesis that treatment with thiamine (vitamin B1) can counter the development of hepatic steatosis driven by overnutrition. Remarkably, the thiamine-treated animals presented with completely normal levels of intrahepatic fat, despite consuming the same amount of liver-fattening diet. Thiamine treatment also decreased hyperglycemia and increased the glycogen content of the liver, but it did not improve insulin sensitivity, suggesting that steatosis can be addressed independently of targeting insulin resistance. Thiamine increased the catalytic capacity for hepatic oxidation of carbohydrates and fatty acids. However, at gene-expression levels, more-pronounced effects were observed on lipid-droplet formation and lipidation of very-low-density lipoprotein, suggesting that thiamine affects lipid metabolism not only through its known classic coenzyme roles. This discovery of the potent anti-steatotic effect of thiamine may prove clinically useful in managing fatty liver-related disorders.
Keywords: Overnutrition; Vitamin B1 Therapy; Fatty Liver